Linking Reading and Writing for Successful Language Learning - Gilma Zuñiga Camacho (Asociación Colombiana de Profesores de Ingles, 2016)
There is a broad consensus in the relationship between reading and writing. Most experts agree that, although not identical, reading and writing are similar and mutually supportive language processes (Butler and Turbil, 1984). Both rely on the reader's or writer's background knowledge to construct meaning and both make use of cueing systems (graphic, semantic, syntactic) to allow the reader or writer to predict and confirm meaning. Traditionally reading and writing have been viewed as two separate processes with little in common, however much of the research is guided by the theory that both reading and writing involve meaning making (Shanahan, 1997).